Correlation of Hamstring Tightness with Balance and Mobility in Young Adults - Huma Akhtar, Pakiza Muskan, Ramsha Amjad, Anza Kaleem Satti, Marwa Javed, Minahil Shahid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Despite of the optimal health regarding metabolic energy levels, physical activity and fitness in young adults, major health concerns are increasing. This increasing dysfunction could be the basic cause for future impairments. Hamstrings muscles are most commonly subjecting to shortening and evaluated for the lower limb resilience. Balance, mobility, muscle strength are important elements to maintain normal functional capacity. The aim of this study was to evaluate Correlation between hamstrings tightness with balance and mobility in young adults. Methodology: A Cross sectional correlational Study was conducted in 385 participants of age 19-24 years old of twin cities i-e Rawalpindi and Islamabad. Passive knee extension test (PKE) was performed to assess hamstrings tightness, whilst Y-Balance test (YBT) for evaluating balance and 6 Minute walk test (6MWT) for Mobility. The measurements are tabulated and analyzed statistically for the Correlation between hamstrings tightness with balance and mobility using SPSS. Results: Sample size of 385 participants with 100% response rate, n= 255 (66.2%) were females while n= 130 (33.8 %) were males. Mean, median for variables along with the SD and Interquartile range was calculated. Correlation was analyzed using spearman’s correlation with the coefficient r (ρ) between mean PKET and 6MWT were ρ= -0.21 and Mean PKET with Dominant side of YBT as ρ= 0.07 while with Non-dominant side as ρ= 0.06. Also, there are no significant differences between dominant and non-dominant sides for PKET and YBT separately as per Wilcoxon signed rank test. Conclusion: Statistically significant weak negative correlation was found in hamstrings tightness with mobility, while there is no significant correlation of hamstrings tightness with balance for both dominant and non-dominant sides. Keywords: Hamstring muscles, Balance, Mobility, hamstrings tightness.